Changes of Work Condition and the Mc Kenzie Ergonomic Intervention Could Decrease of Musculoskeletal Disorder and Work Fatigue Among “Dodol” Industry Workers With Low Back Pain - Ni Nyoman Devi Yani Prabashanti; I Putu Gede Adiatmika; Susy Purnawati (Eduvest - Journal of Universal Studies, 2021)
An unergonomical working condition could cause low back pain due to wrong position. For those condition affected to work production and the worsens is disability.  This study aims to change of work condition by gave break time actively with the solution placed of water and all tools equipment distance, and prevention with McKenzie ergonomic intervention to decrease of musculoskeletal disorders among ‘dodol’ industry workers. This experimental study used treatment by subject design and there were 12 samples study. Period 1 of this study is working condition of process mixing “dodol” without any intervention given by researcher, meanwhile period 2 samples already work with changes strategy based on ergonomic and washing out period, also adaptation held in along period. Low Back pain was measured by Oswestry Disability Index (ODI) and productivity based on comparison product in a day, and score for low back pain measured per work time. Data was analysed with SPSS ver.16 and α=0,05. Results of this research that there was significant difference statistically among variable, and difference of mean is 7,33 or there was decreased of musculoskeletal disorders 10% from 54,31±0,79 to 45,04±0,88. The conclusion of this study that changes of work condition with ergonomic basic could decrease musculoskeletal disorders among “dodol” industry workers with low back pain syndrome at Penglatan, Buleleng Regency.